Synthesis and Spectral Characterization Of Thorium (IV) Complexes With 3-Substituted-4-Amino-5-Mercapto-1,2,4-Triazole Schiff Bases (Global Journal of Science Frontier Research, 2012)
complexes have been synthesized by reacting Th(IV) nitrate with Schiff bases derived from 3-substituted-4-amino-5-mercapto-1,2,4-triazole and glyoxal/ biacetyl/ benzyl in ethanol. These complexes have been characterized on the basis of elemental analysis, molar conductance and spectral studies. Analytical and spectral data suggest structures in which Th(IV) is six coordinated. All these complexes are light yellow in colour and are insoluble in DMF and DMSO. The elemental analysis show that, the complexes analysed for 1:1 stoichiometry of the type, Th.LH 2 (NO 3 ) 4 .Conductance measurement in DMF are too low to account for any dissociation of these complexes in DMF at the concentration of the 10 -3 M.
Keywords: Synthesis; Elemental analysis; Th(IV) complexes